Kajian Status Hara Tanah Sawah Tadah Hujan di Desa Sei Rakyat Kecamatan Panai Tengah Kabupaten Labuhanbatu - Mukklisin Mukklisin; Badrul Ainy Dalimunthe; Fitra Syawal Harahap (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2023)
In the last three years, the production center for lowland rice in Labuhanbatu district, precisely in Panai Tengah District, experienced a decline in production in 2018. One of them was the decline in production due to the decreased nutrient content in the soil and added fertilizer by lowland rice farmers. due to limited land resource data. This study aims to determine the nutrient status of pH and C-Organic of rainfed lowland soil in Panai Tengah Subdistrict, Labuhanbatu Regency with an altitude of 11 meters above sea level. Soil analysis was carried out in the Biology laboratory of the University of North Sumatra. This research was carried out in Labuhanbatu from April 2021 to July 2021. The method in this study was a semi-detailed grid survey with an observation density of 1 sample per 250 meters. Measurement of soil pH using the method of pH-H2O and C-Organic soil using the Walkley and Black method. Based on the Nutrient Status, the pH content of the irrigated paddy soil was classified as very acidic and Slightly Acidic, while the C-Organic and Organic Matter content of the rainfed paddy soil was low so that the effort to improve the nutrient status of the irrigated paddy soil in Sei Rakyat Village, Panai Tengah District, Labuhanbatu Regency was in the form of adding organic matter with compost and fertilizer and inorganic according to the recommendations to improve soil fertility status. Keywords: Nutrient Status, Panai Tengah District, Rainfed Rice Fields